Stock return synchronicity and the market response to analyst recommendation revisions - Devos, Erik; Hao, Wei; Prevost, Andrew K.; Wongchoti, Udomsak (Journal of Banking & Finance, 2015)
In this paper we examine how stock return synchronicity relates to changes in market-based measures of information-based trading in response to analyst recommendation revisions. We find that the market response to analyst recommendations varies according to R2: stocks with lower R2 experience stronger price, trading volume, return volatility, and bid-ask spread reactions in response to revisions of analyst recommendations. The impact of R2 is strongest among smaller companies, suggesting an elevated role for analysts in disseminating information when prices may be less informed. In a multivariate context, these results are robust to the inclusion of additional explanatory variables including firm size. Our results support the premise that R2 is inversely related to the noisiness of the information environment.